Expert Consensus on Effective Management of Chemotherapy-Induced Nausea and Vomiting: An Indian Perspective - Vaid, Ashok K.; Gupta, Sudeep; Doval, Dinesh C.; Agarwal, Shyam; Nag, Shona; Patil, Poonam; Goswami, Chanchal; Ostwal, Vikas; Bhagat, Sagar; Patil, Saiprasad; Barkate, Hanmant (Frontiers in Oncology, 2020)
Chemotherapy-induced nausea and vomiting (CINV) is one of the most common and feared side effects in cancer patients undergoing chemotherapy. Scientific evidence proves its detrimental impact on a patient’s quality of life (QoL), treatment compliance, and overall healthcare cost. Despite the CINV-management landscape witnessing a radical shift with the introduction of novel, receptor-targeting antiemetic agents, this side effect remains a chink in the armor of a treating oncologist. Though global guidelines acknowledge patient-specific risk factors and chemotherapeutic agent emetogenic potential in CINV control, a ‘one-fit-for-all’ approach cannot be followed across all geographies. Hence, in a pioneering attempt, India-based oncologists conveyed easily implementable, region-specific, consensus-based statements on CINV prevention and management. These statements resulted from integrating the analysis of scientific evidence and guidelines on CINV by the experts, with their clinical experience. The statements will strengthen decision-making abilities of Indian oncologists/clinicians and help in achieving consistency in CINV prevention and management in the country. Furthermore, this document shall lay the foundation for developing robust Indian guidelines for CINV prevention and control.